2023
DOI: 10.3390/jpm13020278
|View full text |Cite
|
Sign up to set email alerts
|

A Prospective Study of Longitudinal Risks of Cognitive Deficit for People Undergoing Glioblastoma Surgery Using a Tablet Computer Cognition Testing Battery: Towards Personalized Understanding of Risks to Cognitive Function

Abstract: Glioblastoma and the surgery to remove it pose high risks to the cognitive function of patients. Little reliable data exist about these risks, especially postoperatively before radiotherapy. We hypothesized that cognitive deficit risks detected before surgery will be exacerbated by surgery in patients with glioblastoma undergoing maximal treatment regimens. We used longitudinal electronic cognitive testing perioperatively to perform a prospective, longitudinal, observational study of 49 participants with gliob… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 67 publications
0
2
0
Order By: Relevance
“…Two weeks after the surgery, when patients were discharged home, these risks significantly increased. Notably, for those participants who had a good enough performance status postoperatively to be able to undergo chemotherapy and radiotherapy at 4-6 weeks after surgery, the authors reported that the risks of cognitive deficits reduced and resembled those seen at the presurgical baseline [60]. These findings suggest that there are individual differences in cognitive performance postoperatively and there is a need for personalized cognitive rehabilitation in this population.…”
Section: Cognitive Rehabilitationmentioning
confidence: 95%
See 1 more Smart Citation
“…Two weeks after the surgery, when patients were discharged home, these risks significantly increased. Notably, for those participants who had a good enough performance status postoperatively to be able to undergo chemotherapy and radiotherapy at 4-6 weeks after surgery, the authors reported that the risks of cognitive deficits reduced and resembled those seen at the presurgical baseline [60]. These findings suggest that there are individual differences in cognitive performance postoperatively and there is a need for personalized cognitive rehabilitation in this population.…”
Section: Cognitive Rehabilitationmentioning
confidence: 95%
“…People with glioblastoma are at high risk for developing cognitive deficits due to the presence and location of the tumor, but also due to side effects of surgery, radiotherapy, and chemotherapy [58,59]. In a longitudinal prospective study with 49 participants with glioblastoma undergoing surgery, Sinha et al [60] found that before surgery, the participant risk of deficit was increased in five out of six cognitive domains as compared to normative groups (especially increased risks were to attention, memory, and perception). Two weeks after the surgery, when patients were discharged home, these risks significantly increased.…”
Section: Cognitive Rehabilitationmentioning
confidence: 99%